2017
DOI: 10.1136/bmjsem-2017-000245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a gluteal activation warm-up on explosive exercise performance

Abstract: ObjectivesTo evaluate the effect of a gluteal activation warm-up on the performance of an explosive exercise (the high hang pull (HHP)).MethodsSeventeen professional rugby union players performed one set of three HHPs (with 80% of their one repetition maximum load) following both a control and activation warm-up. Peak electrical activity of the gluteus maximus and medius was quantified using electromyography (EMG). In addition, the kinematics and kinetics of nine players was also recorded using force plate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
17
0
2
Order By: Relevance
“…Similarly, we have recently successfully employed the same musculoskeletal model as in this study to report the effects of an acute intervention on muscular forces during explosive activity. 58 Taken together, these studies therefore demonstrate the unique sensitivity and potential for musculoskeletal models to improve the understanding of problems with clinical relevance. However, to date, we have only used this model to study differences at the cohort level.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, we have recently successfully employed the same musculoskeletal model as in this study to report the effects of an acute intervention on muscular forces during explosive activity. 58 Taken together, these studies therefore demonstrate the unique sensitivity and potential for musculoskeletal models to improve the understanding of problems with clinical relevance. However, to date, we have only used this model to study differences at the cohort level.…”
Section: Discussionmentioning
confidence: 78%
“…The test–retest reliability of FreeBody at the group mean level is particularly important to establish in order to support the use of the model in research which is based on comparing the group mean waveforms of two or more different groups or cohorts—which is often the approach taken in musculoskeletal modeling research. For instance, FreeBody has been used in two recent research projects that sought to quantify the effects of acute (Parr et al, 2017 ) and chronic (Czasche et al, 2017 ) exercise interventions on muscle and joint contact forces. Both of these previous studies demonstrated differences in the group mean waveforms pre and post intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inter-session reliability of FreeBody is currently unknown. In recent years, FreeBody has been used to evaluate the effect of acute and chronic exercise interventions and the model has demonstrated differences in muscle and joint contact forces pre and post intervention(Czasche et al, 2017 ; Parr et al, 2017 ). The aim of this study was, therefore, to assess the reliability of the FreeBody model in order to add support to this previous research and to evaluate the use of FreeBody at the cohort level.…”
Section: Introductionmentioning
confidence: 99%
“…Cleather 7 sensitivity to some of the key assumptions on which it is based (Cleather and Bull, 2010a, 2010bSouthgate et al, 2012) and it has been used to study the effect of exercise interventions on subsequent athletic performance (Czasche et al, 2017;Parr et al, 2017). To this end, only a brief description of the model is provided here, and the interested reader is directed to the previously cited publications.…”
Section: Discussionmentioning
confidence: 99%